2020
DOI: 10.1109/lcomm.2020.2999646
|View full text |Cite
|
Sign up to set email alerts
|

Analog Versus Hybrid Precoding for Multiuser Massive MIMO With Quantized CSI Feedback

Abstract: In this letter, we study the performance of a downlink multiuser massive multiple-input multiple-output (MIMO) system with sub-connected structure over limited feedback channels. Tight rate approximations are theoretically analyzed for the system with pure analog precoding and hybrid precoding. The effect of quantized analog and digital precoding is characterized in the derived expressions. Furthermore, it is revealed that the pure analog precoding outperforms the hybrid precoding using maximal-ratio transmiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…1) Ultra-large fractional bandwidth: With abundant spectrum resource, the fractional bandwidth of THz UM-MIMO systems can be very large, e.g., 16.7% (50 GHz bandwidth at 300 GHz central frequency). By contrast, the fractional bandwidth at microwave and mmWave systems is usually limited, e.g., 0.83% (20 MHz at 2.4 GHz) and 3.33% (2 GHz at 60 GHz).…”
Section: Severe Beam Squint Caused By Thz Peculiaritiesmentioning
confidence: 99%
“…1) Ultra-large fractional bandwidth: With abundant spectrum resource, the fractional bandwidth of THz UM-MIMO systems can be very large, e.g., 16.7% (50 GHz bandwidth at 300 GHz central frequency). By contrast, the fractional bandwidth at microwave and mmWave systems is usually limited, e.g., 0.83% (20 MHz at 2.4 GHz) and 3.33% (2 GHz at 60 GHz).…”
Section: Severe Beam Squint Caused By Thz Peculiaritiesmentioning
confidence: 99%
“…For the inaccurate A t [k] and A r [k], the expressions are similar to (27) while the inaccuracy is enforced on the phase since the amplitude of the elements of these two matrices should be fixed as one, as stated in (2). Fig.…”
Section: B Spectral Efficiency and Energy Efficiency Of The Proposed ...mentioning
confidence: 99%
“…Since the overall dimension of the channel matrix in THz UM-MIMO systems is prohibitively large, acquiring partial elements of the channel matrix is sill difficult. The authors of [20], [26], [27] proposed the hybrid beamforming solutions considering the statistical information of the channel. However, due to the lack of well-known general statistical MIMO channel model in the THz band yet, it is also challenging to know the statistical channel information.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the existing hybrid precoding algorithms based on the single-user system [23][24][25] and the single-antenna multi-user systems [26,27], our work can be applied…”
Section: Computational Complexity Analysismentioning
confidence: 99%
“…In single-antenna multiuser system, it is difficult to jointly consider the changes of user-specific signal quality and multi-user interference. [26] proposed a low-cost hybrid precoding algorithm based on quantized CSI feedback for a single-antenna scenario and revealed that pure analog precoding outperforms hybrid precoding in terms of the ergodic achievable rate under certain conditions, as derived in closed forms with respect to the SNR, the number of users and the number of feedback bits. However, directly quantized feedback still causes a huge amount of overhead to maintain a usable accuracy.…”
mentioning
confidence: 99%